DISHARMONI KEADILAN RESTORATIF PADA PRODUK HUKUM NOMOKRASI - Putri Balqis Salsabila; Muhammad Rustamaji (Sebelas Maret University, 2025)
Observing at Perpol No. 08/2021, Perja No. 15/2020, and Perma No. 01/2024, reveals a number of significant problems that require comprehensive evaluation. Although the three regulations are expected to be an instrument for the transformation of the criminal justice system towards a more humane, responsive, and just approach, a critical study shows that there is an urgent need to conduct a comprehensive review. The main focus of the review includes aspects of definitions, principles, criminal punishment limitations, loss assessment, and criminal offence exceptions. The normative research conducted using primary and secondary legal materials thus uses a conceptual approach that focuses on examining the concept of restorative justice and its disharmony in each legal product. Through deductive syllogism analysis, the research identified disharmony in the implementation of the concept of restorative justice. Fundamental differences are clearly visible in terms of definitions, requirements, and the scope of criminal offences that can be resolved through restorative justice mechanisms.